The Use of Qur'anic Verses as Rajah Pelaris: A Study of Living Qur'an in Jambon Village, Gemawang District, Temanggung Regency - Wahyudi, Nur; Cloritawati, Aprilia; Aliyyah , Muhimmatul; Ulya , Asiqotul; Syafi’, Moh. (Program Studi Pendidikan Agama Islam (PAI), 2023)
Trade is a human effort to meet their needs. However, in trading someone wants instant results and doesn't want to lose, so they do various ways to fulfill their needs, such as using the best selling tattoo with verses from the Koran. The writer found this best selling tattoo practice in one of the villages in Temanggung. The verse used in this practice is QS. Al-Hajj: 27 and QS. At-Tuabah: 111. This research is a field research by collecting data through observation, interviews, and documentation. The purpose of this research is to reveal a living Qur'an phenomenon in the use of Al-Qur'anic verses in the practice of Rajah Rajah. This tattoo is written on a piece of paper on Legi Monday or Legi Thursday, then folded and placed in a wallet or at a trading place by performing sunnah hajat prayers. The function of the two verses is as a form of endeavor to Allah so that he will be given the blessing of life, given halal sustenance such as fast-selling merchandise, as well as motivation to improve trading performance